Use of ICT in Teaching Islamic Studies in Higher Education Schools - Usman Adisa Issa; Hameed Olalekan Bolaji (Universitas Pendidikan Ganesha, 2023)
Information and Communication Technology is currently recognized as a viable and correct educational tool. The application of ICT makes the teaching and learning process simpler, closer, and easier to do anytime and anywhere. The availability and use of ICT tools in the teaching and learning arena is said to be one of the main determinants of the effectiveness of teaching and learning at all levels of education. Islamic Studies is one of the study programs offered in colleges of education in Nigeria that can be taught using ICT. Therefore, this study aims to examine the influence of ICT on the teaching of Islamic studies in universities of education. Three study objectives and research questions were formulated in this research. Descriptive survey research was adopted in this study. The population of this study were all Islamic Studies lecturers in all colleges of education in Kwara State and purposive sampling technique was used to sample respondents in this study. An adapted questionnaire entitled Uses of ICT in Teaching Islamic Studies was used. The main results of the study show that ICT has a significant positive impact on the effectiveness of teaching and learning. This research reveals that the use of ICT, such as computers, the internet, and educational software, has increased student participation and their understanding of Islamic study material. The implication of this research is that these findings highlight the urgent need to strengthen ICT infrastructure and provide adequate access to digital resources to improve the quality of teaching and learning.